Prospects for restoring ecosystems in the Pasvik River basin reconstruction of climate change, biodiversity, history of nature management and conservation practices - Khlebosolova, Olga; Sosna, Evgeniya (Mongolian Journal of Geography and Geoecology, 2025)
The paper is devoted to discussing the effectiveness of measures to restore degraded lands and preserve biodiversity in the north-west of the Murmansk Region in the Pechenga Municipal District (Russian Federation). The purpose of the study was to study climate change, biodiversity, the history of nature management and environmental practices in the basin of the Paz River. Published and archived data from climatic, soil-geobotanical, archaeological, and historical studies were collected and systematized, as well as their own field geoecological studies (2021-2024). The use of reconstruction and forecasting methods made it possible to recreate an objective picture of climatic changes in the basin of the Paz River over the past 9.5 thousand years and to identify a multiple change of vegetation (from Arctic tundra to forest) after the melting of the glacier. The study of archaeological and historical materials allowed us to identify five stages of economic development of the territory, which led to a reduction in biodiversity and land degradation (with a maximum in the 70s of the XX century at the peak of the development of copper-nickel production). Three main factors hindering the restoration of degraded lands in the Paz River basin have been identified: large areas of man-made wastelands with a high content of heavy metals, long-range irradiation of microparticles of pollutants, and low rates of natural restoration of Arctic ecosystems. To accelerate the processes of natural restoration, it is proposed to replace expensive methods of reclamation of man-made wastelands with the creation of a set of conditions for the formation of biological soil crusts (communities of cryptogamous organisms).